Sartre no ensino médio : algumas reflexões sobre o projeto de vida - Mendes, Jallys Martins (2023)
This dissertation aims to develop a theoretical-practical study on the teaching of philosophy in High School related to the competence related to the life project, in accordance with the determinations of the National Common Curricular Base (BNCC). Therefore, the following objectives are presented: 1) develop philosophical workshops based on Sartre's existentialist philosophy; 2) analyze the normative documents of the New High School related to the life project and the teaching of philosophy and; 3) produce teaching material for use by Philosophy teachers regarding work with the life project competency. As a central problem, the following question arises: How can Philosophy classes contribute to the construction of life projects in accordance with the requirements of the New High School and the BNCC guidelines based on the existentialist perspective of Jean-Paul Sartre? To answer this question, we used the works of Sartre, such as Existentialism is a humanism (1973) and Being and Nothingness (2015), and specialists in the areas of existentialist philosophy, education and life project, such as Burstow (2000), Bornheim (2007), Gallo (2012), Freire (1996), Morán (2007) Damon (2009) and Danza (2019). Regarding the methodological aspect, action research, concept pedagogy, active methodologies, philosophical workshop methodology and discourse analysis were used. Therefore, the study presented consists of combining philosophical theory and practice in the classroom, as well as offering a didactic sequence as an educational product for use by Philosophy teachers.